2002
DOI: 10.1080/00221300209602098
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Failures Questionnaire Revisited: Dimensions and Correlates

Abstract: The authors reexamined the factor structure of the Cognitive Failures Questionnaire (D. E. Broadbent, P. F. Cooper, P. Fitzgerald, & K. R. Parkes, 1982) and its correlates. The Cognitive Failures Questionnaire was designed to assess a person's likelihood of committing an error in the completion of an everyday task. A principal components factor analysis with varimax rotation yielded 4 internally consistent, interpretable factors. These factors were labeled Memory, Distractibility, Blunders, and (memory for) Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
199
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(214 citation statements)
references
References 38 publications
12
199
1
2
Order By: Relevance
“…Attention slips and action failures are frequently attributed to situational boredom (Reason & Lucas, 1984;Robertson et al, 1997) and, consistent with this claim, boredom proneness, assessed by the Boredom Proneness Scale (BPS), has been found to be positively associated with the CFQ (Wallace, Kass, & Stanny, 2002;Wallace, Vodanovich, & Restino, 2003). It is also possible that boredom proneness leads to carelessness, and is directly associated with a tendency to make high rates of cognitive and behavioral errors through lack of motivation or effort.…”
Section: Introductionmentioning
confidence: 70%
“…Attention slips and action failures are frequently attributed to situational boredom (Reason & Lucas, 1984;Robertson et al, 1997) and, consistent with this claim, boredom proneness, assessed by the Boredom Proneness Scale (BPS), has been found to be positively associated with the CFQ (Wallace, Kass, & Stanny, 2002;Wallace, Vodanovich, & Restino, 2003). It is also possible that boredom proneness leads to carelessness, and is directly associated with a tendency to make high rates of cognitive and behavioral errors through lack of motivation or effort.…”
Section: Introductionmentioning
confidence: 70%
“…Beyond the issue of consistency with ratings by significant others, it has been demonstrated that the measure possesses internal consistency (Broadbent, et al 1982;Knight et al, 2004), retest reliability, face validity (Knight et al, 2004) and construct validity (Broadbent, et al 1982, Jones & Martin, 2003Wallace, 2004;Wallace et al, 2002). The psychometric properties and construct validity of the everyday memory questionnaire (EMQ) have also been extensively explored in normal (Cornish, 2000) and clinical populations (Efklides et al, 2002;Koltai et al, 1996;Olsson et al, 2006;Schwartz & McMillan, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, three studies examined the underlying structure of the CFQ via factor analysis. The models produced ranged inclusion of three (Broadbent et al, 1982), four (Wallace et al, 2002) and five factors (Pollina, Greene, Tunick, & Puckett, 1992). All articles highlighted memory and action slips as core dimensions measured by the CFQ, whilst perception, distractibility, and interpersonal intelligence were less consistently identified.…”
Section: Dimensions Of Cognitive Failuresmentioning
confidence: 99%
“…Problems with memory and action slips are identified as core dimensions measured by cognitive failures (Broadbent et al, 1982;Pollina et al, 1992;Wallace et al, 2002). However, this tight definition may exclude some aspects of everyday failures such as more general cognitive functioning, distractibility, and mind-wandering.…”
Section: Features Of the Construct Of Cognitive Failuresmentioning
confidence: 99%
See 1 more Smart Citation